Spatiotemporal characterization and hydrological impact of drought patterns in northwestern Morocco - Ait Dhmane, Latifa; Saidi, Mohamed Elmehdi; Moustadraf, Jalal; Rafik, Abdellatif; Hadri, Abdessamad (Frontiers in Water, 2024)
Drought assessment and management, intensified by global warming, present critical challenges in semi-arid Mediterranean regions, impacting environmental sustainability and economic stability. This study evaluates spatiotemporal drought risk in the Bouregreg watershed in northwest Morocco by integrating remote sensing data with various drought indices. The Standardized Precipitation Index (SPI), the Standardized Precipitation Evapotranspiration Index (SPEI), and the Standardized Temperature Index (STI) were utilized to assess meteorological drought over a 12-month period. The Temperature Conditions Index (TCI) was used to evaluate temperature-related conditions for agricultural drought, while the GRACE Drought Severity Index (GRACEDSI) assessed hydrological drought on a monthly scale. Additionally, trend analysis was performed using Mann-Kendall and Sen’s slope methods, and Pearson correlations were conducted among the indices. The findings revealed an overall downward trend in drought indices, with evapotranspiration (SPEI) being the primary drought driver. Over the study period, there was a significant increase in total evaporation demand, largely attributed to rising temperatures (STI and TCI). Meanwhile, precipitation conditions (SPI) remained relatively stable, highlighting the impact of global warming on agricultural and hydrological drought severity patterns in recent years. The results further indicated that drought risk is more pronounced in the plateau and plain areas of the Bouregreg compared to the mountainous regions. In evaluating water reserves, total water storage (TWS) data obtained from the Gravity Recovery and Climate Experiment (GRACE) was utilized. Comparisons were made between in situ groundwater level (GWL) data and those from GRACE TWS at a resolution of 0.25°. Our results reveal concordant trends between the two datasets, despite the differences in resolution. The TWS appears to be strongly correlated with GWL measurements and precipitation data with a lag of 1–4 months. The findings underscored a significant decline in water reserves and worsening drought conditions in recent years. Correlation analyses also revealed a moderate relationship between this decline and the systematic temperature rise, suggesting shared trends influenced by other anthropogenic factors not accounted for in the analysis. In summary, these results underscore the vulnerability of the entire study area to various forms of drought, ranging from mild to extreme severity.